Fractional Local Metric Dimension of Comb Product Graphs - Siti Aisyah; Mohammad Imam Utoyo; Liliek Susilowati (مجلة بغداد للعلوم, 2020)
The local resolving neighborhood  of a pair of vertices  for  and  is if there is a vertex  in a connected graph  where the distance from  to  is not equal to the distance from  to , or defined by . A local resolving function  of  is a real valued function   such that  for  and . The local fractional metric dimension of graph  denoted by , defined by  In this research, the author discusses about the local fractional metric dimension of comb product are two graphs, namely graph  and graph , where graph  is a connected graphs and graph  is a complate graph  and denoted by  We get